Fitting modified HRP-I peptide analogue 3D structure into HLA-DR molecules induces protection against Plasmodium falciparum malaria (2005)
Conserved, high-activity, red blood cell binding malaria peptide 6786, from the HRP-I protein, having a random 3D structure as determined by 1H-NMR, was non-immunogenic and non-protection inducing when used as an immunogen in Aotus monkeys. Modifications made in its amino acid sequence were thus performed to render it immunogenic and protection inducing. Non-immunogenic, non-protection inducing modified peptide 13852 presented A2-H8 and K14-L18 helix fragments. Immunogenic, non-protection inducing modified peptide 23428 presented a short, displaced helix in a different region, whilst immunogenic, protection inducing peptide 24224 had 2 displaced helical regions towards the central region giving more flexibility to its N- and C-terminals. Immunogenic and protection inducing peptides bound with high affinity to HLA-DRB1 0301 whilst others did not bind to any HLA-DRB1 purified molecule. Structural modifications may thus lead to inducing immunogenicity and protection associated with their capacity to bind specifically to purified HLA-DRB1 molecules, suggesting a new way of developing multi-component, subunit-based malarial vaccines.